Material Repertories in Archaeological Sites of the Northern Lowlands of Tucuman (Argentina) - Caria, Mario Alejandro (2024)
The archaeological materiality recorded in two pre-Hispanic sites located inthe lowlands of the province of Tucumán (Argentina) is presented. Therecovered archaeological materials allow us to establish relations of obtaining,production and circulation of non-native and native goods for the region.